2012
DOI: 10.5935/1678-9741.20120081
|View full text |Cite
|
Sign up to set email alerts
|

Aortic pseudoaneurysm as cause of superior vena cava syndrome: a case report

Abstract: The superior vena cava syndrome represents the set of signs and symptoms resulting from obstruction of superior vena cava. The syndrome has as main causes malignant tumors such as bronchogenic carcinoma, lymphoma and mediastinal metastases. Lung cancer accounts for 80% of cases, mediastinal lymphomas by 15% and 5% correspond to other causes. This case report aims to present an unusual case of this syndrome, which occurred in a male patient after penetrating wound in the chest, which developed a pseudoaneurysm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Fukui et al reported a case of SVC syndrome caused by a chronic dissecting aortic aneurysm after aortic valve replacement ( 4 ). Pseudoaneurysms of the ascending aorta or aortic arch -traumatic, infectious or iatrogenic- have been also reported as causes of SVC syndrome ( 5 - 8 ). A rare case of SVC syndrome has been reported in a 8-year old girl as a consequence of long-term use of central venous catheters for hemodialysis ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fukui et al reported a case of SVC syndrome caused by a chronic dissecting aortic aneurysm after aortic valve replacement ( 4 ). Pseudoaneurysms of the ascending aorta or aortic arch -traumatic, infectious or iatrogenic- have been also reported as causes of SVC syndrome ( 5 - 8 ). A rare case of SVC syndrome has been reported in a 8-year old girl as a consequence of long-term use of central venous catheters for hemodialysis ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fukui et al reported a case of SVC syndrome caused by a chronic dissecting aortic aneurysm after aortic valve replacement (4). Pseudoaneurysms of the ascending aorta or aortic arch -traumatic, infectious or iatrogenic-have been also reported as causes of SVC syndrome (5)(6)(7)(8). A rare case of SVC syndrome has been reported in a 8-year old girl as a consequence of long-term use of central venous catheters for hemodialysis (9).…”
Section: Discussionmentioning
confidence: 99%
“…However, symptoms can occur because of the aberrant anatomy, which can lead to compression of mediastinal structures, or because of aneurysm or dissection [1] , [2] . There have been reports of upper extremity deep vein thrombosis (DVT) caused by a giant aneurysm of the ascending aorta [3] , [4] . However, there have been no reports of DVT resulting from an aortic aneurysm of moderate size for which surgery is not indicated.…”
Section: Introductionmentioning
confidence: 99%